2018
DOI: 10.1111/bjh.15712
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunotherapy (RIT) for Follicular Lymphoma achieves long term lymphoma control in first line and at relapse: 8‐year follow‐up data of 281 patients from the international RIT‐registry

Abstract: Summary To assess efficacy of radioimmunotherapy (RIT) in follicular lymphoma, data from 281 patients collected in the RIT Network, with a median follow‐up of 8·2 years after RIT were analysed. RIT was given at first line in 18·5% and at relapse in 81·5%. Following first line therapy, 76·9% achieved complete remission (CR), 9·6% partial remission (PR), 1·9% stable disease (SD) and 1·9% had progressive disease (PD); response was not documented in 9·7%. At relapse, the rate of CR was 48·5% and that of PR was 16·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…During the follow‐up period, secondary malignancy was also reported in 3 of 24 patients (12.5%). In other large RIT registry studies of follicular lymphoma or mantle cell lymphoma that have been followed for a long time, secondary malignancy was reported similarly at 12.4% and 12%, respectively 21–22 The secondary malignancy frequencies reported in both studies were comparable to those in our study. Additional investigation is needed on the prevalence and prognosis of secondary malignancies through long‐term follow‐up RIT studies.…”
Section: Discussionsupporting
confidence: 88%
“…During the follow‐up period, secondary malignancy was also reported in 3 of 24 patients (12.5%). In other large RIT registry studies of follicular lymphoma or mantle cell lymphoma that have been followed for a long time, secondary malignancy was reported similarly at 12.4% and 12%, respectively 21–22 The secondary malignancy frequencies reported in both studies were comparable to those in our study. Additional investigation is needed on the prevalence and prognosis of secondary malignancies through long‐term follow‐up RIT studies.…”
Section: Discussionsupporting
confidence: 88%
“…In the report of the RIT Network (285 FL cases), secondary neoplasms developed in 12.5% (22 solid and 13 hematologic neoplasms, most commonly acute myeloid leukemia and myelodysplastic syndrome), and histologic transformation occurred in 5.7% of cases with a median follow-up of 8.2 years. 27 In our study, the treatment's short-term safety profile was similar to that reported earlier, with 13.0% of cases developing grade 3 or 4 hematologic toxicity of which none urged therapy cessation. Although we had 1 case of acute myeloid leukemia, the follow-up length did not allow us to draw firm conclusions about long-term safety (carcinogenic effects of radiation may manifest 5-10 years later than exposure).…”
Section: Discussionsupporting
confidence: 88%
“…Of note, we did not use the treatment in bulky cases (per the drug's label), and most patients refused external beam radiation therapy. Besides, the proportion of patients receiving 90 YIT in first line (33%) was higher than that observed in the literature (19%), 27 which is probably the consequence of our unique setting (easy-toaccess RIT vs difficult-to-access ASCT; Fig. 1).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The registry is maintained by a professional clinical research organization (CRO; Alcedis GmbH, Giessen, Germany). Further information regarding the EDC system has been published recently [7]. For the analysis presented here, all initially participating centres with documented mantle cell lymphoma (MCL) patients in the RIT-NT were contacted via mail to take part in the extended follow-up for MCL.…”
Section: Methodsmentioning
confidence: 99%